The short- and medium-term distributional effects of the German minimum wage reform - Marco Caliendo; Alexandra Fedorets; Malte Preuss; Carsten Schröder; Linda Wittbrodt (Empirical Economics, 2022)
This study quantifies the distributional effects of the minimum wage introduced in Germany in 2015. Using detailed Socio-Economic Panel survey data, we assess changes in the hourly wages, working hours, and monthly wages of employees who were entitled to be paid the minimum wage. We employ a difference-in-differences analysis, exploiting regional variation in the "bite" of the minimum wage. At the bottom of the hourly wage distribution, we document wage growth of 9% in the short term and 21% in the medium term. At the same time, we find a reduction in working hours, such that the increase in hourly wages does not lead to a subortionate increase in monthly wages. We conclude that working hours adjustments play an important role in the distributional effects of minimum wages.
Keywords: J31; J38; J22; 330; Minimum wage; Wage distribution; Hourly wages; Inequality